Синергія штучного інтелекту та матеріалознавства при створенні зображень НаноАрт на основі структур металів та сплавів - Воденнікова, О.С.; Воденніков, С.А. (Physico-technological Institute of Metals and Alloys, 2026)
In the context of digital transformation and sustainable development, a synergy between artificial intelligence and materials science is emerging. In particular, within the framework of Industry 4.0, researchers in the fields of G8 “Materials Science” and G10 “Metallurgy” focus on the implementation of digital technologies for the creation of “smart” materials, modeling of material properties and structures, automation of production processes, and the development of digital twins, among other areas. This study emphasizes the use of artificial intelligence (AI) to enhance the quality of microfractographic images of metal and alloy structures (including the removal of scratches and dust, as well as improved sharpness, contrast, and grain detail), followed by the creation of NanoArt images in the form of landscapes, animals, objects, and other artistic compositions. As AI-based tools for creating NanoArt images, both specialized scientific software (MountainsMap, Gwyddion, ImageJ/Fiji) and graphic editors with AI support (Adobe Photoshop with the Generative Fill function, Affinity Photo, Luminar Neo), generative neural networks (ChatGPT, Midjourney, Stable Diffusion, Adobe Firefly), and mobile applications (Prisma or Pikazo) can be utilized. The study also examines the application of various AI tools as well as different visual stylizations (e.g., LEGO-style, porcelain style, 3D style, knitted style, puzzle style, and others), which enable the exploration of diverse forms, textures, materials, and visual effects and are significant for the creation of NanoArt and other creative digital images. Special attention is given to the aesthetic aspect of the resulting NanoArt images: the transformation of black-and-white images of metal and alloy structures into multicolored artistic compositions demonstrates the beauty of the microworld and the ability to perceive not only the functional but also the artistic value of research outcomes.